Assessment of autonomic nervous system functions and cardiac rhythms in patients using isotretinoin - Ay, Halil; Aksoy, Mustafa; Güngören, Fatih (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
We aimed to analyze the potential effects of isotretinoin, frequently used in the treatment of acne vulgaris these days. For this purpose, we used the methods of sympathetic skin response (SSR) electrophysiological analysis and electrocardiographic (ECG) analysis in patients using isotretinoin. Thirty patients who were diagnosed with acne vulgaris and treated with oral isotretinoin with a dose of 0.5 mg/kg for at least 1 month were included in the study. In all patients ECG scanning and SSR analysis were performed both before treatment and 1 month after the start of treatment. This study is very important because SSR results show that increasing the existing sympathetic activity in acne vulgaris after isotretinoin usage could explain the exacerbation in acne lesions for the first month, and according to the ECG results the medication did not cause cardiac side effects.